(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The study examines the influence of anxietysensitivity and pain on quality of life of patients with rheumatoid arthritis.The sample of the study was comprised of 140 patients [70 in rheumatoidarthritis (RA) group and 70 in acute pain (AP) group] from a Multi-SpecialtyHospital located in Secunderabad, Andhra Pradesh. A between group design with a cross-section comparison was employed.Themajor findings of the study revealed that patients of Rheumatoid Arthritisgroup scoring high on Anxiety Sensitivity had significantly more score on Pain.The Quality of life however, correlated negatively with Pain suggesting morethe pain reported by the individual, more the Anxiety sensitivity and lowerQuality of life of the individual.